Diagnosis, Treatment Autism - Akeel, Adeeb; Mohammad, Maha (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The research explained autism disorder as a social problem as one of the most complex problems faced by societies in the world and the most important social, psychological and economic effects associated with the existence of a single child in the family And the readiness of families to accept this child, and to highlight the importance of educating the parents to the need for knowledge of all aspects of this disorder, and to guide them to the best ways and methods to deal with autistic children through special training and treatment programs to equip them to continue their life and integration with other children, And to increase the chances of success for them and to help them and their families to face the pressures imposed on them by society.